2018
DOI: 10.3892/etm.2018.6521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression and functional changes of adrenal gland in a rat model of kidney yang deficiency syndrome treated with Sini decoction

Abstract: decoction (SND), a well-known traditional Chinese medicine, has been used to treat kidney deficiency for ~1,800 years. The present study aimed to evaluate the effects of SND treatment on hypothalamic-pituitary-adrenal axis hormones in a rat model of deficiency and to explore the molecular mechanisms using microarray analysis of adrenal glands and adrenocortical cell culture systems. The results indicated that SND treatment recovered circulating serum cortisol, adrenocortical hormone (ACTH) and testosterone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Steroid hormone synthesis pathway is an important pathway in the KYDS model, abnormal steroid levels are common in patients with KYDS. 93,94 In our study, the steroid content in KYDS model of rats was obviously different from the control group, whereas SQP group can effectively reverse 5betapregnane-3,20-dione and pregnenolone in steroid hormone synthesis pathway (P < 0.05).…”
Section: Discussionmentioning
confidence: 64%
“…Steroid hormone synthesis pathway is an important pathway in the KYDS model, abnormal steroid levels are common in patients with KYDS. 93,94 In our study, the steroid content in KYDS model of rats was obviously different from the control group, whereas SQP group can effectively reverse 5betapregnane-3,20-dione and pregnenolone in steroid hormone synthesis pathway (P < 0.05).…”
Section: Discussionmentioning
confidence: 64%
“…For the evaluation of the expression of the KYDS-virus infection patterns, the 10 most frequently used and recommended candidate reference genes from literature were selected ( 17 , 20 , 22 , 28 , 29 ). Following the qPCR assays, the performance of each amplification primer set was examined.…”
Section: Resultsmentioning
confidence: 99%
“…KYDS and influenza A virus subtype H1N1 (A/H1N1) virus infection causes broad ranging variations in gene expression, which form the molecular basis of the biological effects of KYDS following infection with influenza A virus (16)(17)(18)(19)(20)(21)(22)(23). To further understand the mechanisms underlying KYDS following infection with influenza A, with the aim of developing an effective treatment for this disease, the changes in gene transcription during infection need to be determined and understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, genomics has been used to analyze therapeutic targets of CHF and to predict other potential drugs. Tang et al [21] examined therapy using Sini decoction (SND) on kidney yang deficiency in a rat model. Using an mRNA microarray with enrichment analysis, Wang et al found that SND treatment can improve hypothalamic–pituitary–adrenal axis hormones.…”
Section: Application Of Genomics In Chf Researchmentioning
confidence: 99%